Produksi Tanaman Selada Merah Secara Vertikultur dengan Pemberian POC Jakaba : Production of Red Lettuce Plant by Verticulture Using Jakaba POC - A. Farhanah; Hamzah, Faisal; Kaharuddin; Atika; Fariz Pari, Rizfi (Unit Penelitian dan Pengabdian Masyarakat Politeknik Pembangunan Pertanian Gowa, 2024)
Currently, sustainable agriculture is needed to meet human needs in the long term, one of which is the use of organic matter. Jakaba is currently a very interesting novelty to test on plants. Therefore, this study was carried out to determine the effect of Jakaba fertilizer on the production of red lettuce plants verticulturally.The method used was a two-factor Random Group Design with nine types of treatments and three repeats. The first factor is POC Jakaba and the second factor is NPK fertilizer.The results showed that the application of jakaba fertilizer combined with NPK had a significant effect on increasing the height, number of leaves, root volume, and fresh weight of verticulture red lettuce plants and the application of jakaba fertilizer as much as 50% combined with NPK as much as 1 g per plant was effective in increasing the fresh weight of verticulture red lettuce plants. The conclusion obtained is that there is an influence of POC Jakaba on increasing the production of red lettuce plants verticulturally, especially in increasing the fresh weight of the plant.